Executive Director’s Message - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2015)
I am honoured and ready to serve as the next Executive Director of ORNAC and look forward to working with all of you as we take the Association to the next level. It is a privilege to be associated with an organization that, for over 30 years, has been the national voice for Perioperative Registered Nurses across Canada.